ظاهرة الحرقة بين الهوية والهجرة إلى الإنسانية - ربيعي, عبد المالك; سعيدي, محمد (جامعة الوادي - University of Eloued, 2022)
في هذا المقال تناولنا بالدراسة مفهومين هامين جدا الاول مفهوم الهوية والذي اصبح محوريا في اغلب الدراسات والبحوث الاجتماعية والانسانية و ظاهرة الحرقة التي انتشرت بشكل كبير وبين مختلف افراد المجتمع وذلك بقاربة انثروبولوجية من خلال مسالة تمثل الشباب لهذين المفهومين لمحاولة فهم العلاقة بينهما ومدى تاثيرهما في تشكل كل منهما عند الشباب ودورهما بالاساس في اتخاذ قرار الحرقة وهل يمكن اعتبار هذا القرار هجرة الى فضاء اخر موسوم بالإنسانية والحرية وقيم اجتماعية تؤثر بدورها في اتخاذ هذا القرار وذلك بدراسة حالة لشاب جزائري مصاب بمرض القصور الكلوي الحاد والكلي والذي قبل مشكورا مشاركتنا هذا البحث بالمقابلة المباشرة التي تضمنت الاجابات عن تساؤلات مفردات البحث والتي قمنا بمحاولة تحليلها ضمن منظور انثروبولوجي قد يغير في التناول النضري لمفهوم الهوية ومفهوم الحرية ومفهوم الانسانية وكيف تمارس هذه المفاهيم وتتجلى في الواقع المعيش. Abstract: In this article, we dealt with the study of two very important concepts. The first is the concept of identity, which has become central in most social and human studies and research, and the phenomenon of ELHARGA, which has spread widely and among different members of society, through an anthropological approach through an issue of youth representing these two concepts to try to understand the relationship between them and the extent of their impact in shaping each of them. The youth and their role mainly in making the heartburn decision. Can this decision be considered a migration to another space marked by humanity, freedom, and social values that influence its role in making this decision, with a case study of an Algerian young man with acute and total renal insufficiency, who graciously accepted our participation in this research with a direct interview that included the answers On the research vocabulary questions, which we have tried to analyze within an anthropological perspective that may change the theoretical approach to the concept of identity, the concept of freedom and the concept of humanity, and how these concepts are practiced and manifested in the living reality.
مقال
Keywords: الحرقة ؛ الهوية ؛ الهجرة إلى الإنسانية; ELHARGA; identity ; immigration to humanity